Phenotypic and Genetic Heterogeneity in a Thai Glucokinase MODY Family Reveals the Complexity of Young-Onset Diabetes - Thewjitcharoen, Yotsapon; Wanothayaroj, Ekgaluck; Krittiyawong, Sirinate; Nakasatien, Soontaree; Tsoi, Tsz Fung; Lim, Cadmon K. P.; Chan, Juliana C. N.; Himathongkam, Thep (Frontiers in Endocrinology, 2021)
Glucokinase-Maturity-Onset Diabetes of the Young (GCK-MODY) is characterized by asymptomatic, non-progressive and fasting hyperglycemia, albeit not without phenotypic variability. We used next generation sequencing (NGS) to screen for 34 MODY genes in a non-obese person with familial young-onset diabetes followed by screening in 24 family members within three generations with varying presentations of young-onset diabetes and sensorineural hearing loss. The index patient was found to carry a paternally-inherited heterozygous missense variant (c.716 A>G) of GCK in exon 7 with amino acid change (Q239R). This variant was associated with phenotypic heterogeneity ranging from normal glucose tolerance to diabetes with complications amongst the siblings which might be modified by obesity and chronic hepatitis B infection. Two paternally-inherited variants of SLC29A3 encoding a nucleoside transporter protein and Apo-A1 genes also co-segregated with glucose and lipid traits. Co-occurrence of diabetes and deafness in maternal aunts led to discovery of WFS1 (Wolfram syndrome type 1) as a cause of non-syndromic deafness in multiple members of the maternal pedigree. Our findings highlight the complex causes of familial young-onset diabetes and the need of a multidisciplinary approach to interpret the clinical relevance of discoveries made by NGS in this era of genomic medicine.